Schorl-1A from Langesundsfjord (Norway) - Camara,F.; Bosi,F.; Skogby,H.; Hålenius,U.; Celata,B.; Ciriotti,M.E. (Journal of Geosciences, 2022)
A crystal fragment of schorl from Langesundsfjord (Norway), showing a zonation with a biaxial optic behavior in the rim, was studied by electron microprobe analysis, single-crystal X-ray diffraction, Mössbauer, infrared and optical absorption spectroscopy and optical measurements. Measured 2Vx is 15.6°. We concluded that biaxial character of the sample is not due to internal stress because it cannot be removed by heating and cooling. Diffraction data were refined with a standard R3m space group model, with a = 16.0013(2) Å, c = 7.2263(1) Å, and with a non-conventional triclinic R1 space-group model keeping the same hexagonal triple cell (a = 16.0093(5) Å, b = 16.0042(5) Å, c = 7.2328(2) Å, α = 90.008(3)°, β = 89.856(3)°, γ = 119.90(9)°), yielded Rall = 1.75% (3136 unique reflections) vs. Rall = 2.53% (17342 unique reflections), respectively. The crystal-chemical analysis resulted in the chemical formula X(Na0.98K0.01 0.01)Σ1.00 Y(Fe2+1.53Al0.68Mg0.35Ti0.20Fe3+0.20Mn0.02V0.01Zn0.01)Σ3.00 Z(Al5.10Fe2+0.50 Mg0.40)Σ6.00 (Si6O18)(BO3)3(OH)3 [(OH)0.39F0.22O0.39]Σ1.00, which agrees well in terms of calculated site-scattering (X 10.9 epfu, Y 63.7 epfu, Z 83.7 epfu) and refined site-scattering (X 11.4 epfu, Y 63.4 epfu, Z 83.6 epfu). About 0.19 apfu Fe2+ is at the Z sites in the R1 model that showed that one out of six independent Z sites (Zd) has higher refined site scattering [15.5 eps vs. mean 13.7(2) eps for the other five sites] and larger mean bond length [1.969 Å vs. 1.927(6) Å for the other five sites] and larger octahedral angle variance [53° vs. 42(3)°]. All these features support local order of Fe2+ at the Zd site. Optical absorption spectra also show evidence of Fe2+ at the Z sites. The elongation of the Zd-octahedron is along a direction that forms an angle of ca. 73° with a unit-cell edge and is coincident with the direction of the γ-refraction index. All these data support the triclinic character of the structure of the optically biaxial part of the tourmaline sample from Langesundsfjord and provide evidence that even in the presence of excellent statistical agreement factors from excellent X-ray diffraction data, the lowering of symmetry due to cation ordering may have been overlooked in many other tourmaline samples in the absence of a check of the optical behaviour. According to the nomenclature rules, the studied triclinic schorl, should be named schorl-1A.
Keywords: Tourmaline; crystal structure; electron microprobe; Mö ssbauer spectroscopy; infrared spectroscopy; optical absorption spectroscopy